To Determine the Level of Awareness in Respect of Antibiotic Resistance among Health Professionals - Shagufta Haider; S Ali Danish Kazmi; Hasan Shami; Naeema Asghar; Sobia Memon; Musadiq Aziz (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Antimicrobial resistance (AMR) is a major global health problem that makes treating infections more difficult and increases healthcare costs. In Pakistan, the situation is particularly severe. To address this issue, strategies like antimicrobial stewardship and the "One Health" approach are being promoted to encourage responsible use of antibiotics. However, the rising use of antibiotics and a lack of awareness among the public are worsening the resistance problem. This situation underscores the urgent need for immediate action and changes in behavior regarding antibiotic use. Objective: To determine the level of awareness in respect of antibiotic resistance among health professionals Study design: A cross-sectional analysis Duration and place of study: This study was conducted in Gambat Medical College / GIMS Gambat Pakistan from January 2024 to January 2025 Methodology: In this cross-sectional study, 150 health care workers were surveyed through a self-completed questionnaire to assess their knowledge regarding antibiotic resistance. A non-probability consecutive sampling technique was used, and the questionnaire was pilot-tested and validated. All available on-duty healthcare personnel, irrespective of age or professional category, were surveyed. Ethical clearance was obtained, informed consent was taken, and participant anonymity was ensured. Data were statistically analyzed using SPSS version 26, and the findings were expressed in terms of descriptive statistics, tables, graphs, and charts. Results: There were a total of 150 individuals who were a part of this study. The female participants were in majority, representing 66.7% of the total population. All the participants were aged between 19 years to 64 years. The highest cases were from the age group of 25 years to 34 years. 55.3% participants were married. More than half of the participants strongly agreed that antibiotic resistance is the world’s biggest problem. Conclusion: This research suggests varying levels of awareness about antibiotic resistance among health professionals, highlighting the need for ongoing education, training, and targeted interventions to prevent future harm and promote judicious use of antibiotics.